Rethinking the Coral Microbiome: Simplicity Exists within a Diverse Microbial Biosphere - Alejandra Hernandez-Agreda (American Society for Microbiology, 2018)
ABSTRACT Studies of the coral microbiome predominantly characterize the microbial community of the host species as a collective, rather than that of the individual. This ecological perspective on the coral microbiome has led to the conclusion that the coral holobiont is the most diverse microbial biosphere studied thus far. However, investigating the microbiome of the individual, rather than that of the species, highlights common and conserved community attributes which can provide insights into the significance of microbial associations to the host. Here, we show there are consistent characteristics between individuals in the proposed three components of the coral microbiome (i.e., “environmentally responsive community,” “resident or individual microbiome,” and “core microbiome”). We found that the resident microbiome of a photoendosymbiotic coral harbored <3% (∼605 phylotypes) of the 16S rRNA phylotypes associated with all investigated individuals of that species (“species-specific microbiome”) (∼21,654 phylotypes; individuals from Pachyseris speciosa [n = 123], Mycedium elephantotus [n = 95], and Acropora aculeus [n = 91] from 10 reef locations). The remaining bacterial phylotypes (>96%) (environmentally responsive community) of the species-specific microbiome were in fact not found in association with the majority of individuals of the species. Only 0.1% (∼21 phylotypes) of the species-specific microbiome of each species was shared among all individuals of the species (core microbiome), equating to ∼3.4% of the resident microbiome. We found taxonomic redundancy and consistent patterns of composition, structure, and taxonomic breadth across individual microbiomes from the three coral species. Our results demonstrate that the coral microbiome is structured at the individual level. IMPORTANCE We propose that the coral holobiont should be conceptualized as a diverse transient microbial community that is responsive to the surrounding environment and encompasses a simple, redundant, resident microbiome and a small conserved core microbiome. Most importantly, we show that the coral microbiome is comparable to the microbiomes of other organisms studied thus far. Accurately characterizing the coral-microbe interactions provides an important baseline from which the functional roles and the functional niches within which microbes reside can be deciphered.